FAMILY INVOLVEMENT IN ECOLOGICAL DA’WAH THROUGH “SAIPUL BIMBANG” - Patmawati Patmawati; Santa Rusmalita; Wardah Wardah (PSGA LP2M IAIN Pontianak, 2019)
Garbage is a classic problem in our environment, including in Banjar Serasan. The society live on the Kapuas river banks and usually throw the garbage in the river, as the river were a large garbage can that will carry their trash at low tide. They also used the river for bathing and washing, which in turn will also affect their health. This is what makes environmentalists from the village, health center, and maternal and child health services conducted ecological da’wah through “Saipul Bimbang”. It stands for